14. A Comprehensive Real-World Analysis to Compare Adjuvanted Trivalent Influenza Vaccine and Trivalent High Dose Influenza Vaccine by Age and Period of High Influenza Activity for the 2018–19 Season among U.S. Elderly. (31st December 2020) - Postma, Maarten; Pelton, Stephen I; Divino, Victoria; Mould-Quevedo, Joaquin F; Shah, Drishti; DeKoven, Mitchell
Abstract: Background: Influenza vaccine effectiveness decreases with increasing age due to the senescence of immune function and a reduced immune response to antigens. There is also considerable vaccine effectiveness heterogeneity depending on the influenza activity time period, especially in seasons where two different circulating strains predominated, such as the 2018–19 season. This research aimed to assess the effect of age and high influenza activity period (HIAP) on the relative vaccine effectiveness (rVE) of adjuvanted trivalent influenza vaccine (aTIV) vs. trivalent high-dose influenza vaccine (HD-TIV) among elderly (≥65y) recipients in the U.S. Methods: During the 2018–19 influenza season, a retrospective cohort analysis was conducted using professional fee, prescription claims and hospital charge master data in the U.S. The first sub-analysis evaluated rVE for different age groups (65–74 years, 75–84 years, ≥85 years). The second sub-analysis evaluated rVE overall, restricting the observation period from to HAIP: Dec 2018-Mar 2019 (August 2018-July 2019 in the main analysis). Adjusted analyses were conducted through inverse probability of treatment weighting (IPTW) to control for selection bias. Poisson regression was used to estimate the adjusted pairwise rVE for influenza-related hospitalizations/emergency room (ER) visits and office visits. Results: Following IPTW, 561, 315 recipients of aTIV and 1, 672, 779 of TIV-HD were identified. Following IPTW adjustment and Poisson regression, aTIV was more effective in reducing influenza-related office visits compared to TIV-HD (7.0%; 95% CI: 2.6%-11.2%) in the HIAP sub-analysis. In the age sub-analysis, the rVE favoring aTIV ranged from 5.1% (95% CI: -0.17%-10.1%) for the youngest group (65–74) up to 11.4% (95% CI: 0.6%-21.1%) for the eldest group (≥85y) for influenza-related office visits. No statistically significant differences were found for aTIV compared to TIV-HD for prevention of influenza-related hospitalizations/ER visits in the sub-analyses evaluated. Conclusion: In adjusted analyses, aTIV reduced influenza-related office visits compared to TIV-HD within the two older age groups and HIAP sub-analysis. aTIV and TIV-HD demonstrated comparable reductions in influenza-related hospitalizations/ER visits. Disclosures: Maarten Postma, Dr., IQVIA (Consultant) Stephen I. Pelton, MD, Merck vaccine (Consultant, Grant/Research Support)Pfizer (Consultant, Grant/Research Support)Sanofi Pasteur (Consultant, Other Financial or Material Support, DSMB)Seqirus Vaccine Ltd. (Consultant) Victoria Divino, PhD, Seiqrus Vaccines Ltd. (Consultant) Joaquin F. Mould-Quevedo, PhD, Seqirus Vaccines Ltd. (Employee, Shareholder) Drishti Shah, PhD, Seqirus Vaccines Ltd. (Consultant) Mitchell DeKoven, PhD, Seqirus Vaccines Ltd. (Consultant)